Effective Communication Is The Basic Requirements That Regulate The Relationship Between Teacher And Student - Zulfiya Khoshimjonova (Genius Journals, 2024)
Effective communication between teachers and students is essential for creating a conducive learning environment and achieving academic success. This article examines the key requirements for ensuring meaningful and effective interactions in educational settings. By understanding and implementing these key factors, teachers can build strong relationships, increase student engagement, and optimize learning outcomes
Keywords: Educational environment; effective teaching; teachers